AL AQSA DELUGE: THE POETIC CONTRIBUTION FROM ARABIC CRITICS AND POETS - Murtdha Ayad Mohammed (Scholars Digest Publishing, 2025)
This research explores the role of modern Arabic poetry in expressing political struggle, resistance, and national identity, with a special focus on the Palestinian cause. It shows how poetry has served as a powerful and emotional tool for expressing the pain of oppression, the desire for freedom, and the voice of people facing injustice. Through poems, many Arab poets were able to show their support for Palestine and reflect the deep connection between the Palestinian issue and the Arab world. The research also highlights the presence of Jerusalem in poetry, showing how this city represents more than just a place it becomes a symbol of history, culture, religion, and identity. In addition, the study discusses how poets describe both the city and the village, revealing deep feelings of belonging, exile, and the loss of home. Another important part of the research is the use of nature in Palestinian poetry, where elements like the moon, the sun, mountains, and other natural symbols are transformed into representations of resistance, hope, endurance, and the deep connection to the land. This study shows that poetry in the Arab world, especially Palestinian poetry, is not only a reflection of reality, but also a way to preserve memory, defend identity, and inspire future generations.
Keywords: Palestinian Poetry, Resistance, Identity, Nature, Jerusalem, Modern Arabic Poetry, Revolution, National Struggle, Village and City, Cultural Expression.